Could Country-by-Country Reporting Increase Profit Shifting? - Ruby Doeleman; Dominika Langenmayr; Dirk Schindler (CESifo GmbH, 2024)
Since 2016, Country-by-Country reporting has provided tax authorities with detailed information about multinationals' worldwide activities. It has been hailed as a game-changer for corporate taxation, enabling tax authorities to target multinational firms with high profits in tax havens. We model Country-by-Country reporting as increasing both tax planning and audit costs for profit-shifting multinationals, where the latter costs depend on the share of profits held in tax havens. Then, Country-by-Country reporting makes shifting profits from a high-tax country to a tax haven relatively more attractive than shifting from a low-tax country to a tax haven—a substitution effect. Thus, while the total amount of profits shifted to the tax haven decreases, profit shifting from high-tax affiliates may increase relative to the situation without Country-by-Country reporting. We confirm these changes in profit-shifting patterns using a staggered difference-in-differences design. The opposing effects for low-tax and high-tax countries also help explaining the mixed findings of previous empirical studies on Country-by-Country reporting.
Keywords: H25; H26; F23; 330; country-by-country-reporting; profit shifting; anti-tax-avoidance rules